Green Approach for Manufacturing of Polymer Surface Structures with Microcavities Having Robust Chemically Functionalized Inner Surfaces - Zimmermann, Philipp; Schlenstedt, Kornelia; Schwarz, Simona; Vehlow, David; Blanke, Marit; Fery, Andreas; Nagel, Jurgen (ACS Applied Polymer Materials, 2022)
Polymer surface modification is a key step in manufacturing for applications of parts in biotechnology, catalysis, sensing, and other fields. However, functionalization approaches with sufficient robustness are often connected with the use of harsh chemical treatment and/or high-energy consumption. We present a versatile approach for chemical functionalization of polymer surfaces, which is compatible with fused filament fabrication, is energy efficient, and does not require harmful chemicals. The modification takes advantage of embedding of polyethylenimine-coated calcium carbonate particles into polymer melts and subsequent dissolution of the particles allowing for further modification of the residual polyethylenimine. The process results in surfaces that are hierarchically structured and feature undercuts, rendering them robust against wear and tear as well as increasing the specific area available for functionalization. We show proof-of-concept functionalization with dyes, metal layers, and metal nanoparticles, demonstrating the versatility of our concept and discuss the potential for catalysis and biotechnology.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 3d printing; grafting; metal plating; polymer surface modification; surface structure